The Influence of Mental, Physical, Ethical and Entrepreneurial Skills on Innovative Abilities of Technical and Vocational Education and Training Graduates - Oribo , Calleb M. (African Journal of Education,Science and Technology (AJEST), 2018)
The main objective of TVET is to produce competent, employable and self-reliant graduates but majority of TVET graduates lack practical hand-on skills needed by the industry rendering them unemployable. This research investigated the influence of mental, physical, ethical and entrepreneurial skills on innovative abilities of TVET graduates. The aim of this study was to assess whether mental, physical, ethical and entrepreneurial abilities promote TVET graduates innovativeness. This study was conducted through a survey research design. Purposive and stratified sampling techniques were used to select the sample for the study. The data was analyzed by use of the Statistical Package for Social Sciences (SPSS) computer program. This study adopted the Gestalt theory which states that stimuli only have meaning as they are cognitively organized by a person. Learning is based on changes in perceptual process; thus true learning, or insight, occurs when the individual perceives new relationships with the field and if a person does not understand how to use a certain tool, insight will not occur until he or she figures out the relationship between the tool and its function. The study’s conceptual framework illustrates the relationship between mental, physical, ethical, entrepreneurial skills and innovativeness of TVET graduates. In this study mental, physical, ethical, entrepreneurial abilities are the independent variables while TVET graduate innovativeness is the dependent variable. The employees who were innovative in the industry indicated that the TVET education they went through integrated mental, physical, ethical, entrepreneurial skills training. TVET education should integrate mental, physical, ethical, entrepreneurial skills training to produce innovative TVET graduates. TVET graduate who will be equipped with mental, physical, ethical, entrepreneurial skills will be innovative and self-reliant for sustainable development.